Investigations on the Reactivity of Copper(I) Complexes with a N3S Thioether Ligand System. Issue 6 (21st December 2022) - Rotärmel, Thomas; Specht, Pascal; Becker, Jonathan; Neuba, Adam; Schindler, Siegfried
Abstract: In the active site of several copper monooxygenases, thioether residues are coordinated through the sulfur atom, e. g. dopamine‐ β ‐monooxygenase (D β M). The reaction of dioxygen with a series of copper(I) complexes with thioether groups in tripodal ligands based on either derivatives of tris(2‐pyridylmethyl)amine (TMPA) or a guanidine system were investigated by low‐temperature stopped‐flow measurements. The formation of labile intermediates, an end‐on superoxido complex, and μ ‐1, 2‐ trans‐ peroxido copper(II) complexes were spectroscopically detected and a kinetic analysis allowed the calculation of activation parameters for these reactions supporting the postulated mechanism. Most interesting was the finding that replacing the ethyl group in the tren‐guanidine derivative ( TMG Et)2 (SEt Et )N with a methyl group allowed a dramatic increase in the stability of the formed superoxido copper complex. Measurements with ozone were performed in order to find an alternative way to obtain and stabilize the labile intermediates. Abstract : A copper(I) complex with a tripodal ligand containing a sulfur thioether residue formed a ɳ 1 ‐superoxido complex with dioxygen at −90 °C. The complex could be spectroscopically characterized, and the formation of this complex was analyzed. Furthermore, related copper(I) complexes were investigated which formed μ ‐1, 2‐ trans ‐peroxido complexes.